Automatic 4-mirrors system for alignment of high-power laser radiation - V.V. Toporovsky; A.G. Alexandrov; I.V. Galaktionov; A.L. Rukosuev; A.V. Kudryashov (Компьютерная оптика)
This paper presents the automated system for minimizing the deviation of the path of passage and the divergence of a secondary radiation source with parameters similar to ones of the main beam of a high-power Ti:Sa laser using mirrors in kinematic mounts on the motorized stages. As an alignment laser, the diode laser with a fiber output was used with radiation characteristics coinciding with the parameters of the main beam (wavelength, beam diameter). The successive approximation algorithm was used to minimize the beam deflection. The positioning accuracy and beam size matching were analyzed on the near-field camera and were equaled to 28.6 µm along the X-axis and 26.4 µm along the Y-axis. Beam size mismatch was equaled to 0.151 mm. The pointing accuracy was analyzed on the far-field sensor and equaled 15.34 µrad along the X axis and 12.03 µrad along the Y axis. The curvature of the wavefront was 0.06 µm.